2009
DOI: 10.1590/s1676-06032009000200004
|View full text |Cite
|
Sign up to set email alerts
|

Body size and extinction risk in Brazilian carnivores

Abstract: Body size and extinction risk in Brazilian carnivores. Biota Neotrop., 9(2): http://www.biotaneotropica.org.br/v9n2/en/ abstract?article+bn00509022009.Abstract: Because extinctions are not random across taxa, it is important for conservation biologists to identify the traits that make some species more vulnerable. Factors associated with vulnerability include small geographical ranges, low densities, high trophic level, "slow" life histories, body size, and tolerance to altered habitats. In this study we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
1
6
0
1
Order By: Relevance
“…The effects of habitat loss are primarily felt by large mammals, as suggested by Swihart et al (1988) and Forero-Medina et al (2009). In agreement with the tendencies found by the studies cited, we found in this study that for medium-and large-sized mammals in the QF, the species with greater body weights were more sensitive to disturbance.…”
Section: Discussionsupporting
confidence: 92%
“…The effects of habitat loss are primarily felt by large mammals, as suggested by Swihart et al (1988) and Forero-Medina et al (2009). In agreement with the tendencies found by the studies cited, we found in this study that for medium-and large-sized mammals in the QF, the species with greater body weights were more sensitive to disturbance.…”
Section: Discussionsupporting
confidence: 92%
“…All of these data may allow for conservation actions to be taken sooner rather than later, with early action being more cost-effective and more successful (Fisher and Owens 2004). Jones et al (2003) conducted a multivariate analysis of correlation between extinction risk in bats (represented by IUCN threat level) and various natural history and morphological traits known to correlate with extinction risk in other taxa (Purvis et al 2000;Isaac et al 2005;Forero-Medina et al 2009). Jones et al (2003) found extinction risk to be highly correlated with evolutionary history, meaning clades shared similar levels of threat.…”
Section: Estimating Extinction Risk and Extinction Rate: The Role Of mentioning
confidence: 99%
“…There are about 6,399 mammal species, 701 of which are distributed in Brazil and of which 194 can be considered medium-and large-sized (Paglia et al 2012;Burgin et al 2018). Due to recurring threats to the remaining populations, most mammal species, especially those of medium and large size, are under risk of extinction in Brazil (e.g., Grelle et al 2006). Previous empirical works have demonstrated that mediumand large-sized mammals are specifically sensitive to the effects of fragmentation (Chiarello, 1999;Calaça et al 2010;Magioli et al 2016) and changes in the landscape configuration (Garmendia et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous empirical works have demonstrated that mediumand large-sized mammals are specifically sensitive to the effects of fragmentation (Chiarello, 1999;Calaça et al 2010;Magioli et al 2016) and changes in the landscape configuration (Garmendia et al 2013). Such threats affect medium and large sized mammals primarily due to the characteristics of this group, such as low population density (Grelle et al 1999), small litter size and long gestation period (Brown 1995), and body size (Forero-Medina et al 2009). In addition, behavioral characteristics such as activity patterns can be influenced by fragmentation processes (Norris et al 2010).…”
Section: Introductionmentioning
confidence: 99%